PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 2 TANJUNG MEDANG - Purna Irawan; Otang Kurniaman; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the fact that the students' learning outcomes are low. This can be seen from the value of science students with an average of 65.21. The percentage of students who reached the KKM only 44% of the 25 students, thus the total number of students who completed only 11 people. The purpose of this study is to improve the learning outcomes of science students of Class V SD Negeri 2 Tanjung Medang North Rupat District with the application of cooperative learning model type make a match. Research Instrument consists of Learning Device which used in this research is based on Education Unit Level Curriculum (KTSP) or known as Curriculum 2006. Learning tool consists of syllabus, RPP, student worksheet and observation sheet. Teacher activity during the learning process using cooperative type learning make a match has increased. In the 1st cycle of the 1st meeting with an average of 62.5 at the 2nd meeting an average increase of 75. After the 1st cycle the 1st meeting increased by an average of 83.33 and increased at the 2nd meeting with an average of 87 , 5 with very good category. Student activity during the learning process with the application of cooperative learning model type make a match has increased. The 1st cycle encounters a student activity with an average of 58.33 meetings 2 with an average of 62.5. In the second cycle of the 1st meeting with an average of 70.83 continues to increase at the second meeting with an average of 79.17